2020
DOI: 10.1021/acsabm.0c00031
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient Isolation of Tumor Cells by a Three Dimensional Scaffold Chip for Diagnosis of Malignant Effusions

Abstract: High efficient detection of effusion tumor cells (ETCs) has great clinical significance to identify malignant from benign effusions, but few strategies are designed to enrich and identify tumor cells from effusions. Herein, we developed a three-dimensional scaffold microchip (3D scaffold chip) which could efficiently isolate individual ETC and ETC cluster (ETC/cluster) from pleural effusions and ascites by molecular recognition and physical obstruction. The 3D scaffold chip could enrich ETCs with 94.7% capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although numerous clinical features are different between MPE patients and patients with BPE, the clinical significance of a single index in the discrimination between the two conditions is quite limited due to either its low sensitivity or specificity. In recent years, with the development of analytical approaches, the construction of mathematical models based on multiple markers has been increasingly applied in the field of medicine [26] , [27] , [28] , [29] , [30] . This approach combines a series of significant parameters to generate a predictive model to achieve a better diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous clinical features are different between MPE patients and patients with BPE, the clinical significance of a single index in the discrimination between the two conditions is quite limited due to either its low sensitivity or specificity. In recent years, with the development of analytical approaches, the construction of mathematical models based on multiple markers has been increasingly applied in the field of medicine [26] , [27] , [28] , [29] , [30] . This approach combines a series of significant parameters to generate a predictive model to achieve a better diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work [ 24 ], we succeeded to design a three dimensional scaffold microchip which could efficiently isolate individual effusion tumor cell (ETC) and ETC cluster from effusions. Then we used logistical regression analysis to create a three-marker (effusion CEA, ETC count and ETC cluster count) predictive model, and this predictive model obtained excellent diagnostic performances both in the training and validation sets.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Alexandrakis et al 8 reported a scoring model including TP, LDH, TNF-α, C4, and haptoglobin, with an accuracy of 89% in the overall date and 70% in the cross-validation date. Tian et al 48 also calculated scores for diagnosing malignant ascites, including innovative features-effusion CEA, effusion tumor cells (ETC), and ETC cluster count, with an AUC of the training dataset and validation dataset of 0.939 and 0.948, respectively. We also developed a predictive score model for the same purpose.…”
Section: Discussionmentioning
confidence: 99%